2014
DOI: 10.1021/jp4096198
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Hydrogen Sulfide in Liquid Water and at the Water–Vapor Interface Using a Polarizable Force Field

Abstract: Molecular dynamics (MD) simulations using the Drude polarizable force field are used to study the solution and interfacial properties of hydrogen sulfide (H2S) in water. Pairwise H2O-H2S Lennard-Jones interactions were optimized to the experimental H2S gas solubility at 298 K. These parameters yield hydration free energies and diffusion coefficients for H2S that are in good agreement with the experiment over 273-323 K and 298-368 K, respectively. H2S is sparingly soluble in water, with a ΔG(hydr)° of -0.5 kcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 69 publications
(106 reference statements)
9
43
0
Order By: Relevance
“…This is consistent with previous studies that concluded that thiol sulfurs are poor hydrogen bond acceptors due to their large radius and modest electronegativity. 19,39 These rdfs are consistent with the thiols being hydrophobic solutes, with very limited hydrogen bonding interactions with the aqueous solvent.…”
Section: Methylthiolsupporting
confidence: 59%
See 1 more Smart Citation
“…This is consistent with previous studies that concluded that thiol sulfurs are poor hydrogen bond acceptors due to their large radius and modest electronegativity. 19,39 These rdfs are consistent with the thiols being hydrophobic solutes, with very limited hydrogen bonding interactions with the aqueous solvent.…”
Section: Methylthiolsupporting
confidence: 59%
“…Ab initio molecular dynamics (AIMD) has been widely used to study the hydration structure of solutes. [15][16][17][18][19][20] These simulations can provide a first-principles representation of the solvent-ion structure. This is especially valuable for thiolates because there is little experimental data to describe their solution structure.…”
Section: Introductionmentioning
confidence: 99%
“…The Lennard-Jones parameters are typically assigned empirically such that simulations using these parameters accurately predict the properties of representative bulk liquids (e.g., density, enthalpy of vaporization, dielectric constant, etc. ), 10,[12][13][14][15][16][17] although some QM-based approaches have also been applied. [18][19][20][21][22] A drawback of parameterizing Lennard-Jones parameters empirically is that they are generally underdetermined when molecules contain multiple types of atoms, allowing widely different parameters to be defined for them.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this conventional nonpolarizable model, the Drude polarizable force field is also supported by CHARMM . This model has been parameterized for water, ions, sulfur‐containing compounds, aromatics, amides, alkanes, alcohols, proteins, and nucleic acids …”
Section: Introductionmentioning
confidence: 99%